Effect of Spray Drying on Protein Content of Natural Rubber Serum (NRS) - M.N. Zairossani, I. Aimi Izyana and (IIUM Engineering Journal, 2011)
Natural rubber latex comprises approximately 70% natural rubber serum (NRS) which is the aqueous part of the latex. The NRS is made up of mainly water and non-rubber components; sugar, protein and other lipids. The protein component of the NRS is separated using membrane separation and spray dried whereby the amino acid and protein content was monitored during the process. The optimum drying temperatures were first determined to obtain the maximum recovery of the protein powder, whereby the amino acid content was approximately 40 times that of the feed. The production of protein powder from NRS increases the rubber industry's competitiveness through value addition to the previously discarded NRS but also to the processing industry. NRS protein powder has a great opportunity to be developed as an alternative protein source. ABSTRAK: Susu getah asli mengandungi lebih kurang 70% serum getah asli (natural rubber serum (NRS)) iaitu bahagian susu getah yang berair. NRS sebahagian besarnya merupakan air dan komponen bukan getah; gula, protein dan lipid-lipid lain. Komponen protein NRS dipisahkan dengan menggunakan membran pemisah dan kaedah kering semburan dimana asid amino dan kandungan protein dipantau semasa proses tersebut. Pada mulanya, suhu pengeringan optimum ditentukan untuk mendapatkan hasil maksima serbuk protein, dimana kandungan asid amino adalah lebih kurang 40 kali suapan. Penghasilan serbuk protein daripada NRS meningkatkan daya saing industri getah dan industri pemprosesan menerusi pertambahan nilai terhadap NRS yang sebelum ini hanya dibuang. Serbuk protein NRS mempunyai peluang besar untuk dimajukan sebagai sumber protein alternatif. KEY WORDS: protein, spray dry, natural rubber serum.